Patient reported experiences of health care, quality of life and preoperative information in colon cancer - Maria Reinwalds; Charlotta Larsson; Rode Grönkvist; Eva Angenete (Acta Oncologica)
Background and purpose: Cancer may create problems and needs associated with impaired quality of life (QoL). The first health care encounter is important to enable patients to cope and may ultimately impact QoL. The aim of this study was to describe the patients’ experiences of encounters with health care professionals. Another aim was to explore the possible impact that the encounters may have on QoL 1 year after a colon cancer diagnosis. We also wanted to investigate whether patients had received information about treatment related side-effects.